Distributional shifts in a biodiversity hotspot. (December 2018) - Beaudrot, Lydia; Acevedo, Miguel; Lessard, Jean-Philippe; Sheil, Douglas; Larney, Eileen; Wright, Patricia; Ahumada, Jorge
Abstract: Identifying ongoing changes in the distributions of species is critical for understanding and conserving biological diversity. Distributional shifts have been demonstrated in many ecosystems and taxa, yet the extent and nature of these changes remain largely undocumented for tropical forest mammals. Shifts over short time periods can be particularly alarming in areas of the world where mammals are already under threat as a result of human activities. This is the case for Madagascar, an island where deforestation, hunting, invasive species, and other human threats have resulted in the extinction of several endemic species. Here, we ask, are the distributions of Malagasy mammals changing? We test this by modeling local colonization and extinction dynamics, which are the biological processes that produce distributional shifts. We use camera trap data from the TEAM Network for four species along a 570 m elevational gradient in Ranomafana National Park, Madagascar. The endemic Eastern red forest rat ( Nesomys rufus ) declined in overall occupancy while the non-native bushpig ( Potamochoerus larvatus ) increased in occupancy overall. The two endemic carnivore species shifted their elevational use: the Malagasy ring-tailed mongoose ( Galidia elegans ) retracted from higher elevations and the Malagasy civet ( Fossa fossana ) moved to higher elevations, likely in response to anthropogenic pressures. These results show that shifts are occurring and we can detect them with just six years of data. These results appear near unique in documenting rapid changes in the spatial distributions of tropical forest mammals and provide important information for conservation. Highlights: Identifying changes in species distributions is critical for conservation An endemic Malagasy rodent ( Nesomys rufus ) declined in overall occupancy while a non-native bushpig ( Potamochoerus larvatus ) increased in occupancy overall. Two endemic Malagasy carnivore species shifted their elevational use, likely in response to anthropogenic pressures. Documentation of rapid changes in the spatial distributions of tropical forest mammals is near unique and provides important information for conservation